Scientific Text as a Basis of Teaching Russian as a Foreign Language to Students Majoring in Economics - Санина, Л. П.; Копылова, Е. В.; Хуен, Ле Минь (Teaching Languages at Higher Educational Establishments at the Present Stage. Intersubject Relations, 2016)
The peculiarities of the scientific text as a main unit of training Russian to foreign students majoring in economics are considered in the article. Some components of structural integrity of the text, allocated for training, are analyzed. Special attention is focused on the semantic content of text materials which is characterized by certain elements. It is specified that in the analysis of structural integrity of the text it is necessary to consider that, on the one hand, each text type is under construction on the certain model including a number of components (the title, the introduction, etc.), on the other hand, structural integrity of the text is provided with the existence of special means of an interphrase connection in it. The authors review principal tools of the interphrase connection taking into account that the semantic part of the text represents a theme-rheme chain. The violation of the chain continuity means the border of the text semantic parts. In the analysis of the structural and semantic organization of the text it is necessary to allocate a formally semantic structure, which can include a final part, where the results are summed up, the means of interphrase communication are isolated, the logical conclusions are drawn. The special system of tasks for work with the text has to be aimed at the development of the analysis skills, the independent producing and registration of communicatively-completed texts. The methodical principles of training the text, considered in the article, are implemented in manuals for foreign students of non-linguistic departments majoring in economics. Their training includes learning such disciplines as the economic theory, audit, business fundamentals, finance and credit, public administration by economics, international economic relations and tourism. The article outlines the prospects for further researches aimed at the selection and organization of work with scientific texts of the economic content for interactive training.